How to train your dragon book 3 : how to speak Dragonese - Cowell, Cressida (New York : Little, Brown and Company, 2010)
Young Viking hero Hiccup Horrendous Haddock III must save his friend Fishlegs from Roman soldiers and learns to communicate in Dragonese to prevent a full-scale war.
Originally published in the U.K. by Hodder Children$1 (Bs Books, 2005.s
Keywords: Vikings -- Fiction; Dragons -- Fiction; Kidnapping -- Fiction; Friendship -- Fiction; Adventure stories; Humorous stories